POLA PERILAKU KONSUMSI KELUARGA PENERIMA MANFAAT PKH (PROGRAM KELUARGA HARAPAN) DI KELURAHAN PEJAGAN KECAMATAN BANGKALAN KABUPATEN BANGKALAN - Imama, Wahyu Nur; Yulistiyono, Herry (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of this study was to determine how consumption patterns of behavior before and after the family received PKH assistance in Pejagan Village, Bangkalan District, Bangkalan District. The research method used is descriptive qualitative, with a focus of research on the consumption patterns of PKH beneficiary families. Data collection methods are done by interview, observation, and documentation. Data analysis techniques were performed using data reduction, presentation, and drawing conclusions. To test the validity of the data using source triangulation. The results showed that the implementation of the Family Hope Program in Pejagan Sub-district, Bangkalan District, Bangkalan District had gone well because the distribution process to poor households was in accordance with procedures. The main objectives of the Harapan Families Program are to break the poverty chain, improve the quality of human resources, and change behavior that is less supportive in improving welfare. In this study welfare measurement is seen from household consumption patterns. It is known that the acceptance of the Family Hope Program assistance received by RTSM is sufficient to reduce the burden of household expenses on children's education costs. While in the household there are various kinds of needs both food and non-food